2020
DOI: 10.1007/s10640-020-00444-x
|View full text |Cite
|
Sign up to set email alerts
|

Linking Human Destruction of Nature to COVID-19 Increases Support for Wildlife Conservation Policies

Abstract: This paper investigates if narratives varying the cause of the COVID-19 pandemic affects pro-wildlife conservation outcomes. In a pre-registered online experiment (N = 1081), we randomly allocated subjects to either a control group or to one of three narrative treatment groups, each presenting a different likely cause of the COVID-19 outbreak: an animal cause; an animal and human cause (AHC); and an animal, human or lab cause. We found that the AHC narrative elicited significantly greater pro-conservation poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 54 publications
1
30
0
1
Order By: Relevance
“…The swift and interventionist responses to COVID-19 may also enable decision action on climate change through growing preferences for harder climate and biodiversity policies like taxes and regulation. For instance, Shreedhar and Mourato (2020) found that people expressed higher support for commercial wildlife trade bans -a 'hard' conservation policy tool with wide-ranging implications -when they were informed that infectious zoonotic diseases, of which COVID-19 may be one, are linked to anthropogenic environmental change. Apart from enabling a swift reaction to other crises, experiencing the COVID-19 pandemic may lead to greater awareness, which in turn could result in policy spillovers.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…The swift and interventionist responses to COVID-19 may also enable decision action on climate change through growing preferences for harder climate and biodiversity policies like taxes and regulation. For instance, Shreedhar and Mourato (2020) found that people expressed higher support for commercial wildlife trade bans -a 'hard' conservation policy tool with wide-ranging implications -when they were informed that infectious zoonotic diseases, of which COVID-19 may be one, are linked to anthropogenic environmental change. Apart from enabling a swift reaction to other crises, experiencing the COVID-19 pandemic may lead to greater awareness, which in turn could result in policy spillovers.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…For those communities of practice, COVID-19 has underscored issues with the sustainability and safety of contact between humans and wildlife, and concerns about how unsustainable practices could contribute to the future emergence of novel coronaviruses or similar pandemic threats. [1][2][3] More broadly, these conversations have pointed to a broader need to address the upstream drivers of poor health and disease burden outside of pandemic settings. In the One Health or planetary health tradition, pandemics can be viewed the product of several proximate drivers (eg, climate change, biodiversity loss, land degradation), all of which share an ultimate cause: the explosion of consumption, and destruction of the natural world, caused by capitalism, globalisation, colonialism and neoliberal economic policies.…”
Section: Introductionmentioning
confidence: 99%
“…On a practical note, helping people understand the links between the human impact on the environment and climate change with infectious disease outbreaks is likely to help increase public understanding and engagement (Amelung et al, 2019;Roh et al, 2015;Shreedhar & Mourato, 2020). Scholars have suggested that emphasising the links between experiences of extreme weather events and climate change facilitates a congruent cognitionemotion link, likely the most successful approach (van der Linden, 2014).…”
Section: Discussionmentioning
confidence: 99%